The effects of PGF2α and CIDR on ovarian antral follicular development and plasma IGF-1 concentration in goats. - Bukar, Muhammad Modu; Omar, Mohamed Ariff; Yusoff, Rosnina; Haron , Abd Wahid; Dhaliwal, Gurmeet Kaur; Naing, Soh Win; Goriman Khan, Mohd Azam (Medwell Publishing, 2011)
The aim of this study was to determine the effects of oestrus synchronization with PGF2α, and CIDR on the ovarian antral follicle population and plasma IGF-1 concentration in goats. Daily transrectal ultrasonographic examination was conducted in 24 regularly cycling goats that were divided equally into 3 groups and oestrus synchronized with PGF2α, (group A), CIDR (group B) and unsynchronized group (C). The mean number of follicles and IGF-1 concentration was significantly higher in the synchronized and subsequent natural oestrous cycles of group A and B when compared to group C. The total number of 3mm diameter follicles were significatly higher in groups A and B compared with the control group C while the follicles that were 6mm and larger were not significantly different (p>0.05). There was a significant low positive correlation (r = 0.14, N = 234) between IGF-1 concentration and the number of 3mm follicles and between plasma IGF-I concentration and number of follicles (r = 0.13, N = 234). In conclusion, oestrus synchronization with PGF2α, or CIDR was associated with increased plasma IGF-1 concentration and number of follicles compared with naturally cycling goats.